Penentuan Zona Kerentanan Longsor Berdasarkan Karakteristik Geologi dan Alterasi Batuan - Anastasia Dewi Titisari; Hitznaiti Zaidini' Khul Husna; Ilham Dharmawan Putra; I Gde Budi Indrawan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
ABSTRACT Landslide is one of the most frequent disasters in Indonesia. The occurrence of landslides is heavily controlled by geological conditions especially in areas with composed by altered rocks. Hargotirto Village, Kokap District, Kulon Progo Regency, DIY is composed by altered rocks so that many landslides occur.It is necessary, thereforeto determine the landslide susceptibility zone based on the geological characteristics and rock alteration in the area as one of disaster mitigation efforts to reduce the risk of landslide disaster. The research method used is data collection in the field such as inclination data of slope, geological condition, and land cover; and laboratory analysis such as petrographic analysis, XRD (X-Ray Diffraction) analysis, and rock geochemical analysis using ICP-AES (Inductively Coupled Plasma - Atomic Emission Spectroscopy).The collected data are used as parameters for landslide zonation determination using Analytical Hierarchy Process (AHP) method.The results showed that the lithology of the research area is andesite and porphyry diorite with alteration type of argillic and propylitic alteration. Their intensity are categorized as low to moderate alteration.Based on these conditions can be categorized into4 levels of landslide susceptibility namely the very high landslide susceptibility that dominates 35% of research areas in the north and northwest; the high landslide susceptibility of 20% spreads over the center of the study area; the moderate landslide susceptibility of 20% distributed in the center southernof the study area; and the low landslide susceptibility of 25% spread over the southern part of the study area.Therefore, residents who live in the area are advised to always be alert to the possibility of landslide because it is included in the zone of very high and high landslide susceptibility. Keywords: argillic alteration; Hargotirto; landslide susceptibility; prophyllitic alteration